2013
DOI: 10.4187/respcare.02487
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Smoking, Depression, and Anxiety on Mortality in COPD Patients: A Prospective Study

Abstract: BACKGROUND: Smoking, depression, and anxiety increase the risk of death in patients with COPD, but the combined effect of these factors is unknown. We assessed the interactive effects of smoking, depression, and anxiety on mortality in patients with COPD. METHODS: We collected and analyzed data from 7,787 subjects with COPD, in 14 rural communities, from May 2008 to May 2012, and used logistic regression to evaluate the interactions and relative excess risk due to interaction (RERI). We applied the attributabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…[44][45][46] Depressed patients also have lower self-confidence, greater feelings of hopelessness, and increased apathy. 6,47 Depression contributes to suboptimal disease control due to poor self-care and lack of motivation to seek help, resulting in nonadherence to medication, 48 less likelihood of quitting smoking, 49,50 and poor participation in pulmonary rehabilitation, 51 leading to ineffective COPD management.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] Depressed patients also have lower self-confidence, greater feelings of hopelessness, and increased apathy. 6,47 Depression contributes to suboptimal disease control due to poor self-care and lack of motivation to seek help, resulting in nonadherence to medication, 48 less likelihood of quitting smoking, 49,50 and poor participation in pulmonary rehabilitation, 51 leading to ineffective COPD management.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore a one-year prospective study reported baseline depression was associated with persistent smoking, longer hospitalization stay, increased symptom burden, poorer physical and social functioning, and increased mortality [22]. Lou and co-workers [24] in a prospective study (n = 7,787) investigated the impact of current smoking, depression on mortality in patients with COPD. Their findings indicated that patients who were current smokers with depressive symptoms were at four folds increase the risk of death.…”
Section: Impact Of Depression On the Course Of Copdmentioning
confidence: 99%
“…Depression also increases severity of COPD due to its effect on early addictive smoking and impediment of smoking cessation 7 . In addition, non COPD-related outcomes of depression include longer hospitalization 8 , mortality 9 , impaired functional status, poor exercise capacity 8 , poor quality of life 10 , non-adherence to medical treatment, and sleep disturbances 8 .…”
Section: Introductionmentioning
confidence: 99%